Exploring the impact of robotics program in enhancing students’ attitude towards science - Sabariah Sharif; Thiwagar Muniandy; Muralindran Mariappan (Global Academic Excellence (M) Sdn Bhd, 2023)
The use of educational technology tools and program in education has been vital in Malaysia due to its benefits. Although many studies have proven these programs benefits for students’ academic improvement, very less studies have focus on students’ improvement towards attitude. Hence, the objective of this research was to explore the impact of robotics program in enhancing students' attitude towards Science. The study involved 474 10 years old students from the states of Selangor and Malacca, Malaysia. A quantitative research design was employed, utilizing a quasi-experimental approach with a control group and an experimental group using pre-test and post-test measurements. A questionnaire was administered to both the experimental and control groups to collect the necessary data. The collected data were analysed using Repeated Measures Analysis of Variance (ANOVA) test, with a significance level of 0.05, using SPSS 25 software. The results indicated a significant change (α ≤ 0.05) in the attitude towards science for the experimental group that received the robotics program, as compared to the control group.